Constructing an evaluation framework for primary pharmacovigilance systems in developing countries: a case study from China - Lei, Shuang; Lin, Shuzhi; Zhu, Xiaoying; Liu, Wei; Liu, Qian; Yin, Lin; Feng, Bianling (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to develop an evaluation framework for primary pharmacovigilance systems based on the Chinese context, with potential applicability to regions with similar system maturity. The framework was informed by the WHO manual and tailored to national policies and resource constraints to support consistent pharmacovigilance practices in similar settings and enhance medication safety.MethodsThis study employed semi-structured interviews, literature review, brainstorming, group discussions, and other common methods to establish a preliminary indicator system. The Delphi Method was employed to screen indicators at various levels based on inclusion principles. Subsequently, the Analytic Hierarchy Process (AHP) was applied to determine indicator weights.ResultsThe effective response rates for both rounds of questionnaires were 100%. Furthermore, the coefficients of reliability were 0.87 and 0.88 for each round, and the Kendall’s W for the process and outcome indicators were 0.173 and 0.236. The significance tests for Kendall’s W were both P < 0.001. The final evaluation indicator system consisted of 3 first-level indicators, 9 second-level indicators, and 35 third-level indicators.ConclusionThis study developed a practical and context-sensitive evaluation framework for primary pharmacovigilance systems in China. The framework offers a feasible assessment tool and may serve as a reference for regions with similar development stages or incomplete pharmacovigilance systems, providing guidance for system improvement and resource allocation.